Oxide based ceramic matrix composites for high temperature aerospace sealing applications - Pirzada, TJ (2021)
This thesis looks at the viability of using oxide based ceramic matrix composites for high temperature gas turbine sealing applications. Two material systems namely Nextel312/SiOC, Nextel 312 fibre with SiOC matrix, and Nextel720/Alumina, Nextel 720 fibre with alumina matrix, were studied in detail and modified in order to produce CMC variants that could perform adequately as seals materials.